THE IMPACT OF POPULATION IMMIGRATION ON THE LABOUR MARKET OF THE UNITED KINGDOM - Kasnauskienė, Gindra; Vėbraitė, Loreta (Ekonomika, 2013)
Abstract. The impact of immigration on the labour market has become a very important subject of public and political debates in recent years. The aim of this study was to estimate the impact of immigration on the labour market of the United Kingdom in 1991–2010. Using a system of equations for immigration, unemployment, wage and gross domestic product, the structural vector error correction model and linear regression models were developed. The application of the structural vector error correction model has shown that immigration has a negative impact on the country’s labour market in the short run as it reduces real wages and increases unemployment. The linear regression models have indicated that immigration, ceteris paribus, negatively influencesunemployment and real wages in the long run.Key words: immigration, labour market, impact, short run, long run